The Future of Artificial Intelligence in Accounting - N. A. Nikiforova (Учёт. Анализ. Аудит, 2025)
The business landscape is being reshaped by artificial intelligence’s (AI) process automation and data aggregation. The consequence of this change is in accounting, where concerns about the unlimited use of automated processes are widespread. The paper aimed to comprehensively examine current trends and forecasts and to analyze the potential impact of these technologies on various areas of human activity and social processes. AI rapidly advances, offering opportunities for improved production, quality of life, and problem-solving. AI-powered systems can settle complex problems autonomously. Formulating and testing hypotheses, logical reasoning, and content analysis are foundational to major research methods. This allows to accumulate analytical material and review all the information collected during the research. The paper examines AI’s strengths and weaknesses to highlight its similarities and differences in human intelligence. The author explores AI’s history to set the stage for a discussion of its future effects on accounting. Also, the author analyzes these publications to predict the future of accounting in an AI-driven workplace. Artificial intelligence cannot easily replace human qualities. This study’s results, accessible to a broad audience, reveal that AI’s impact on accounting extends beyond automation and efficiency gains to a fundamental reshaping of the accountant’s organizational function. Professionals ready for a rapidly changing digital world will find new opportunities here.